Equity concrete issues in the European Union : The role of cultural and artistic actors - Autissier, Anne-Marie (2007)
Cultural diversity is the only possible way of developing EU integration. This objective has to be seen from a general interest viewpoint, without any discrimination towards any kind of population – be it with European origins or not. From this viewpoint, cultural justice has a lot to do with the recognition of the non Europeans’ contribution to the emerging European public space.